THE INFLUENCE OF MOTIVATION, THE QUALITY AND PERFORMANCE DATA MANAGEMENT CIREBON ONE REGARDING WHICH DATA ON LOCAL GOVERMENT CIREBON CITY - Ma’aruf Nuryasa; Abdul Aziz (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — This observe goals to reap statistics approximately have an impact on among the unbiased variables Data Manager Motivation, Data Management Quality, and Data Manager Performance at the established variable, specifically CSD Services on the Cirebon City Government, each independently -alone (partial) or together (simultaneously). Research method— This study makes use of quantitative studies strategies via way of means of engaging in direct surveys in the field. The populace on this observation had been all CSD Data Managers from each Regional and Non-Regional Apparatuses. Based on the calculation of the Slovin formula, the pattern used is one hundred samples with the pattern choice approach the usage of Stratified Random Sampling. Result— The three unbiased variables have power on CSD offerings via way of means of 51.1%, the ultimate 48.9% is motivated via way of means of different variables out of doors the observe. Conclusion— In this observation, there are four predominant conclusions, specifically (1) Data Manager Motivation has a high-quality impact on CSD Services in Cirebon City, which means that if Data Managers have accurate motivation, CSD Services will even get better. Vice versa, if the Data Manager does now no longer have motivation, then the CSD Service will even decline. (2) The best Data Manager has a high-quality impact on CSD Services in Cirebon City, which means that if the Data Managers have accurate best, the CSD Services will be even better. Vice versa, if the Data Manager does now no longer have accurate best, then the CSD Service will even decline. (3) The overall performance of the Data Manager has a high-quality impact on CSD Services withinside the City of Cirebon, which means that if the Data Manager has awesome overall performance, the CSD Services will even get better. Vice versa, if the Data Manager does now no longer have an awesome overall performance, then the CSD Service will even decline. (4) Taken together, the three variables studied have an impact on CSD Services in Cirebon City with a correlation price of 0.715 or excessive high-quality dating occurs.